Analisis Terhadap Panggilan Sidang Kepada Para Pihak Melalui Domisili Elektronik dan Surat Tercatat Berdasarkan Perma No. 7 Tahun 2022 Tentang Perubahan Atas Perma No 1 Tahun 2019 Tentang Administrasi Perkara dan Persidangan Di Pengadilan Secara Elektronik - Herlinca Nababan; Mustaqim; Hotma P. Sibuea (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
In order to use advances in information and technology in the world of justice, the Supreme Court issued Perma Number 7 of 2022. Before this regulation came into force, summons for court proceedings and notification of decisions were carried out by court officials called bailiffs, but with the enactment of Perma Number 7 of 2022, summons for court and notification of the decision or decision is made via electronic domicile or by the post office, in which case the Supreme Court has collaborated with PT Pos Indonesia (Persero) to use a document delivery service to the intended case party. The principles of justice that are simple, fast and low cost have not been achieved properly because after the summons document or decision notification has been made by the bailiff then the summons is carried out through the intermediary of the post office officer, here the post office in the delivery process has not been on target, so it is returned to Court. The post is actually fast, but many letters are returned for reasons such as the house in question is empty, the address is not known and the person in question has moved, so the judge will deliberate to make a general summons. Thus, the principles of justice that are simple, fast and low cost are not achieved.